Workplace Bullying and Psychological Well-being: The Mediating Role of Perceived Social Support at a Selected Government Department - MTutuzeli Dywili (Re-engineering Business Processes in the New Normal - The Business and Economic Development Post COVID-19 and the Restructuring of the Global Economy: Proceedings of 8th International Conference on Business and Management Dynamics, 2023)
Orientation: The well-being of an employee is severely affected when that employee is continuously exposed to stressful environments such as a bullying environment. When employees feel that they are not receiving the protection and support they perceive they are supposed to be getting they often resign from their positions. The failure to provide an environment that is free from bullying behaviour will result in an organisation incurring heavy financial loses. It is essential for an organisation to be able to control such behaviour thus create a conducive environment that does not affect employee’s self-esteem and self-confidence. Research Purpose: This study seeks to examine the negative effects of workplace bullying as a stressor on employees’ psychological wellbeing and how the availability of social support can reduce the negative effects of bullying. Motivation for the Study: Bullying in the workplace has been recognised as an international problem due to its increasing magnitude and the harmful consequences on individuals and organisations. Research Approach, Design and Method: The study used the quantitative approach to test the hypothesis, a sample of 276 employees at the Department of Education were used. Main Findings: The study findings provide evidence that workplace bullying is a stressor that impacts the psychological wellbeing of individuals which can be buffered by the existence of social support. Practical/Managerial Implications: The current study results suggested that perceived social support mediates the relationship between workplace bullying and psychological wellbeing. As indicated earlier on that workplace bullying seem to be prevalent in the department of education though to a small extent it can be recommended that the department put in place various initiatives that increase employees’ perceptions of being supported. Promoting an environment that allow employees to accept one another, being involved and that promote transparency is key in making employees feel at home and can contribute towards combating workplace bullying. Involving employees and showing great concern for their welfare contributes significantly towards increasing their perception of receiving social support. Through accepting one another, it will be rare for employees to subject one another towards such a negative act. Such initiatives create a favourable working environment where workplace bullying is less prevalent. Contributions/Value-add: Significant relationships were found to exist on all these tested study hypotheses leading to the rejection of all study null hypothesis. The study main hypothesis was tested and the study can conclude that the relationship between workplace bullying and psychological well-being is mediated by perceived social support.